Ventajas y desventajas del uso de vitamina c (acido ascórbico) en el cultivo de camarón (litopenaeus vannamei) - Loayza Abarca, Bryan Steeven (Machala : Universidad Técnica de Machala, 2021)
Ecuador throughout history has been characterized as one of the largest producers of white shrimp (Litopenaeus vannamei) worldwide, likewise, it has been called internationally as "The best shrimp in the world" due to its nutritional quality, high quality organoleptic properties. Shrimp farming in Ecuador has gone through one of the most disastrous stages in terms of production, one of the without problems is the appearance of diseases where the prevalence was manifested in the time of the 2000s due to the white spot. The use of inputs that has manifested itself in shrimp farming as a result of the "White Spot" is vitamin C or "Ascorbic acid". Vitamin C has been used thanks to the different parameters that benefit and enhance the cultures of aquatic organisms. The use of vitamin C helps tissue regeneration, reduces stress in aquatic organism cultures, and also helps disinfect water. Within the cultivation of white shrimp (Litopenaeus vannamei) among the best-known advantages we have: help in each process as an anti-stress, chloride regulator, tissue regenerator, strengthening of mineral exchanges. Among the disadvantages currently it can be said that it occurs due to poor management, within these is the deficiency of vitamin C for growth, the overdose in the improvement of water quality with respect to chlorides. One of the exclusive disadvantages is black death. Forming necrosis of both the muscle and the exoskeleton.
El Ecuador a lo largo de la historia se ha caracterizado por ser uno de los productores de camarón blanco (Litopenaeus vannamei) más grandes a nivel mundial, asimismo, se lo ha denominado a nivel internacional como “El mejor camarón del mundo” debido a su calidad nutricional, propiedades organolépticas de alta calidad. El uso de insumos que se ha manifestado en el cultivo de camarón a raíz de la “Mancha Blanca”. Uno de los insumos es la vitamina C o “Ácido ascórbico”. La vitamina C se ha utilizado gracias a los diferentes parámetros que benefician y potencian a los cultivos de organismos acuáticos. El uso de vitamina c ayuda a la regeneración de tejidos, disminución del estrés en cultivos de organismos acuáticos, asimismo, ayuda en la desinfección del agua. Dentro del cultivo de camarón blanco (Litopenaeus vannamei) entre las ventajas más conocidas tenemos: ayuda en cada proceso como anti estresante, regulador de cloruros, regenerador de tejidos, fortalecimiento de los intercambios de minerales. Dentro de las desventajas actualmente se puede decir que se da debido al mal manejo, dentro de estos esta la deficiencia de vitamina c para el crecimiento, la sobredosis en el mejoramiento de calidad de agua con respecto a cloruros. Una de las desventajas exclusivas es la muerte negra o black death. Formándose la necrosis tanto del musculo como el exoesqueleto.
Keywords: CAMARÓN; VITAMINA; ENFERMEDADES; CRUSTÁCEOS